Life Cycle Assessment of Renewable Energy Sources - Singh, Anoop; Pant, Deepak; Olsen, Stig Irving; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Governments are setting challenging targets to increase the production of energy and transport fuel from sustainable sources. The emphasis is increasingly on renewable sources including wind, solar, geothermal, biomass based biofuel, photovoltaics or energy recovery from waste. What are the environmental consequences of adopting these other sources? How do these various sources compare to each other? Life Cycle Assessment of Renewable Energy Sources tries to answer these questions based on the universally adopted method of Life Cycle Assessment (LCA). This book introduces the concept and importance of LCA in the framework of renewable energy sources and discusses the key issues in conducting their LCA. This is followed by an in-depth discussion of LCA for some of the most common bioenergy sources such as agricultural production systems for biogas and bioethanol, biogas from grass, biodiesel from palm oil, biodiesel from used cooking oil and animal fat, Jatropha biodiesel, lignocellulosic bioethanol, ethanol from cassava and sugarcane molasses, residential photovoltaic systems, wind energy, microalgal biodiesel, biohydrogen and biomethane. Through real examples, the versatility of LCA is well emphasized. Written by experts all over the globe, the book is a cornucopia of information on LCA of bioenergy systems and provides a platform for stimulation of new ideas and thoughts. The book is targeted at practitioners of LCA and will become a useful tool for researchers working on different aspects of bioenergy.
Importance of Life Cycle Assessment of Renewable Energy Sources -- Key Issues in Conducting Life Cycle Assessment of Renewable Energy Sources -- Life Cycle Assessment of Agricultural Production Systems with Main Emphasis in Biogas and Bioethanol Production -- Life Cycle Assessment of Biomethane from Lignocellulosic Biomass -- Life Cycle Assessment of Biodiesel from Palm Oil -- Environmental Sustainability Assessment of Ethanol from Cassava and Sugarcane Molasses in a Life Cycle Perspective -- Comparison of Algal Biodiesel Production Pathways using Life Cycle Assessment Tool -- Sustainability of (H2+CH4) by Anaerobic Digestion via EROI approach and LCA evaluations -- Life cycle assessment of wind energy -- Comparing various indicators for the LCA of residential photovoltaic systems -- Hydropower Life-Cycle Inventories: Methodological Considerations and Results Based on a Brazilian Experience -- Comparison of Various Life Cycle Assessment of Different Renewable Energy Sources.
Keywords: Energy; Renewable energy resources; Renewable energy sources; Alternate energy sources; Green energy industries; Sustainable development; Energy; Renewable and Green Energy; Renewable and Green Energy; Sustainable Development; Electronic books